A prognostic model based on 10 gene signatures associated with intestinal microbiota predicts survival prognosis of esophageal squamous cell adenocarcinoma. Issue 1 (31st December 2022) - Du, Jiang; Qiao, Han; Xie, Dalong
Abstract : This study aimed to construct a potential prognostic model for the clinical prediction of esophageal squamous cell adenocarcinoma (ESCA), based on intestinal microbiota-related genes. Microbiome, transcriptome, and clinical phenotype data were downloaded from the TCMA, UCSC, and GEO databases. Intestinal microbiota-related prognostic genes were screened using differential- and univariate Cox regression analyses. The ESCA subtypes were explored based on prognostic genes, followed by infiltration analysis of immune cells in the different subtypes. Feature genes were identified using LASSO and multivariate regression analyses, and a prognostic model was established and validated. Univariate and multivariate Cox regression analyses were used to identify independent prognostic factors. The amount of Bacteroidetes and Proteobacteria differed significantly between the tumor and paracancerous samples. A total of 17 intestinal microbiota-related prognostic genes were also screened. We then identified three ESCA subtypes that exhibited significant differences in microbiota distribution and immune cell infiltration. Finally, we identified 10 gene signatures that were significantly associated with the survival status of ESCA patients. Furthermore, patients with no immunotherapy response presented a significantly higher risk score and prognostic risk. We constructed a prognostic model based on 10 characteristic genes related to intestinal microbiota, which could potentially predict the prognosis of ESCA patients.